Karakterisasi Hidrogel sebagai Absorben Metanil Yellow dari Kulit Pisang Kepok - Nurlatifah, Ismi; Arlianti, Lily; Kanya Riyadi, Giska; Amyranti, Mutia; Kurniasari, Ratih; Maftukhah, Siti (UNISTEK, 2025)
Environmental pollution due to textile industry waste, especially synthetic dye waste, has become increasingly widespread and has become a serious concern in recent decades. Dyes such as Metanil Yellow are often found polluting waters, causing adverse impacts on ecosystems and human health due to their toxic and difficult-to-decompose nature. This study aims to identify the characteristics of hydrogels made from kepok banana peels in absorbing and degrading Metanil Yellow dye. The research methods used include organoleptic tests to determine the physical characteristics of the hydrogel, water absorption tests to measure the capacity of the hydrogel to absorb liquids, and dye degradation tests using a UV-Vis Spectrophotometer to determine the effectiveness of the hydrogel in absorbing Metanil Yellow dye. The results showed that the hydrogel had a smooth texture, had the highest water absorption capacity of 81.30% hydrogel with the addition of 0.6 grams of Sodium Tripolyphosphate, and the highest degradation of Metanil Yellow dye, which was 46.95% at a concentration of 10 ppm. %. Hydrogels made from kepok banana peels have the potential to be used as absorbers of Metanil Yellow dye.